2009
DOI: 10.1097/aln.0b013e31819db2c4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flumazenil on Bispectral Index Monitoring in Unpremedicated Patients

Abstract: This study demonstrates that flumazenil given to healthy unpremedicated patients during propofol/remifentanil anesthesia significantly increased the BIS value and allowed earlier emergence from anesthesia. This may indicate that flumazenil could be used on a case-by-case basis to reverse endogenous or exogenous endozepines that might play a role during anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Human EEG data gathered during recovery from general anesthesia characteristically exhibits an increase in high-frequency power 3638 . Our results are also consistent with those of Dahaba et al, who determined that flumazenil changed the frontal EEG of patients undergoing intravenous anesthesia towards a pattern more indicative of awakening 39 . In humans, increased power in higher frequency bands is also more indicative of the lighter stages of sleep (such as N1 and REM) 40 more common in the early morning in preparation for waking.…”
Section: Discussionsupporting
confidence: 93%
“…Human EEG data gathered during recovery from general anesthesia characteristically exhibits an increase in high-frequency power 3638 . Our results are also consistent with those of Dahaba et al, who determined that flumazenil changed the frontal EEG of patients undergoing intravenous anesthesia towards a pattern more indicative of awakening 39 . In humans, increased power in higher frequency bands is also more indicative of the lighter stages of sleep (such as N1 and REM) 40 more common in the early morning in preparation for waking.…”
Section: Discussionsupporting
confidence: 93%
“…26 Furthermore, in a recent prospective randomized clinical trial, administration of flumazenil intraoperatively during propofol/remifentanil anaesthesia in healthy unpremedicated patients not previously exposed to any benzodiazepine medication significantly increased BIS value. 11 It has also been demonstrated that flumazenil improves recovery of high cortical and neuromotor functions following halothane, enflurane and isoflurane anaesthesia, reduces shivering and improves the overall quality of emergence. 27 References to convulsions and ventricular tachycardia precipitated by flumazenil have been reported in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…11 Naturally occurring endozepines, or endogenous benzodiazepine receptor ligands, that did not result from environmental contamination with pharmaceutical benzodiazepines have been isolated in different mammalian tissues. 11,21,22 Specifically, endogenous benzodiazepines were detected in potentially physiological concentrations in human cerebrospinal fluid, serum, plasma, urine, ultrafiltrates of patients who had not received benzodiazepines and breast milk of healthy, newly delivered women who were not taking benzodiazepines. [5][6][7][8]23,24 Benzodiazepines of natural origin (NBZDs) have been isolated in medicinal plants and foods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations